(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The present research concentrates about compare the behaviour of concrete filled FRP tubes under different grades of concrete. Evaluate the behaviour of concrete filled FRP tubes using central holes with and without an inner PVC pipe. To evaluate both fully and partially concrete filled FRP tubes attain the axial compressive strength, tensile load and Modulus of elasticity. Comparison of strengths for the above cases and suggesting the effectiveness of FRP. Compared with conventional concrete cylinders, FRP tubes filled with concrete attains a compressive strength, which is 87 % higher that of conventional concrete cylinders. Strength and ductility are greatly improved by filling the tubes with concrete. FRP tubes were more efficient than steel tubes in this regard. Concrete in the compression zone is partially confined as evident by the lateral tensile strains measured on the shell. If the hole is maintained by an inner PVC pipe, the confinement effectiveness is improved and could approach that of a totally filled tube. It can be observed that there is significant improvement in Cylinder Compressive Strength, Split Tensile Strength and Modulus of Elasticity compared to PVC Shells. The Percentage increase in Compressive Strength for M20 Grade of Concrete with Central Hole dia of 0mm, 50mm & 75mm are 87.76%, 54.31% and 71.11 respectively. Similarly, for M25 Grade of Concrete with Central Hole dia of 0mm, 50mm & 75mm are 106.93%, 81.79% and 93.46% respectively.